Evaluation Of the Cipp Model Program in Implementing the Toefl Test at Upt Universitas Sembilanbelas November Kolaka - La Ode Muhammad Idrus Hamid B; Muchlas Suseno; Samsi Setiadi (Journal of International Multidisciplinary Research, 2024)
This research aims to evaluate the implementation of the TOEFL test at Sembilanbelas November University Kolaka using the CIPP (Context, Input, Process, Product) evaluation model. The research method used is evaluation research with a qualitative approach. This research sample involved the Language UPT of Sembilanbelas November Kolaka University as the research subject, with a focus on the implementation of the TOEFL test and related programs. Data was obtained through observation, in-depth interviews and documentation studies. The collected data was analyzed using the data analysis model from Miles and Huberman, which includes data reduction, data presentation and conclusion drawing stages. The research results show that the implementation of the TOEFL test at the UPT Bahasa Sembilanbelas November Kolaka University has several weaknesses, especially related to inadequate physical facilities, lack of training for instructors, and lack of flexibility in the test implementation schedule. Despite this, the program was successful in improving participants' English language skills, although there is still a need to focus more on developing broader practical and communication skills. This evaluation provides recommendations for improvement and further development in the implementation of the TOEFL test program, with the hope that these steps will improve the quality of test implementation and provide a greater contribution to students' academic and professional progress.